Energy, environmental and economic sustainability in East Asia policies and institutional reforms - Lee, Soocheol; Pollitt, Hector; Fujikawa, Kiyoshi 1959- (Routledge, 2020)
"This book looks at institutional reforms for the use of energy, water, and resources toward a sustainable future in East Asia. The book argues that developments in the East Asian region are critical to global sustainability and acknowledges that there is an increasing degree of mutual reliance among countries in East Asia-primarily China, Japan, Korea and Taiwan. It analyzes environmental impacts stemming from the use of energy, water and mineral resources via economic development in East Asia in the medium to long term (through 2050) through theoretical and empirical modelling. The book also evaluates the ripple effects of environmental and resource policies on each country's economy and clarify the direction of institutional reform in energy systems, resources, and water use for a sustainable future"--
Description based on print version record
Keywords: Sustainable development / East Asia; Environmental management / East Asia